1993
DOI: 10.1002/1097-0142(19931015)72:8<2389::aid-cncr2820720816>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in advanced stage squamous cell cancer of the cervix

Abstract: Background. This study was undertaken to review prognostic factors for advanced squamous cell cancer of the cervix. Methods. A clinicopathologic review of patients diagnosed with advanced stage squamous cell cancer of the cervix was performed at the University of Michigan Medical Center, Ann Arbor, Michigan, from 1970–1985. Results. All patients had squamous cell disease and were divided according to the following stages: Stage IIIa (4), Stage IIIb (113), Stage IVa (32), and Stage IVb (26). The cumulative 5‐ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 27 publications
1
26
0
2
Order By: Relevance
“…Our results are similar to those of Hopkins and Moreley [1] and Fallon et al [2]. When renal failure occurred, all patients were dead of disease by 16 months [1].…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Our results are similar to those of Hopkins and Moreley [1] and Fallon et al [2]. When renal failure occurred, all patients were dead of disease by 16 months [1].…”
supporting
confidence: 92%
“…When renal failure occurred, all patients were dead of disease by 16 months [1]. Abnormal IVP was a risk factor that decreased survival rate to 20% of that of patients with normal IVP [2].…”
mentioning
confidence: 99%
“…Because the data linking obesity to increased cervical cancer is limited, it seems more likely that the excess mortality could be either the result of a lack of screening in obese women or a detrimental impact of obesity on treatment outcomes. In contrast to the large population studies just mentioned, several smaller retrospective studies have not shown obesity to be a factor that negatively influences survival in women with cervical cancer (94,95).…”
Section: Cervical Cancermentioning
confidence: 73%
“…(14, 15) A more recent larger retrospective study of 738 cervical cancer patients demonstrated that a higher BMI was associated with a more favorable outcome. (16) The authors did not report any adverse influence of BMI on outcomes.…”
Section: Discussionmentioning
confidence: 99%